2017
DOI: 10.1109/jlt.2017.2698044
|View full text |Cite
|
Sign up to set email alerts
|

Relative Humidity Sensing Using a PMMA Doped Agarose Gel Microfiber

Abstract: Humidity sensors rely on humidity-induced refractive index change in the sensing material despite the sensor configuration. Polymer-based microwires can absorb water vapor molecules and detect humidity changes without the need of further coating. However, the sensitivity-simplicity trade-off is still a challenge. Sophisticated coating methods, complex resonating structures, and nanostructured films are reported as methods to enhance the device sensitivity. A simple technique, to build a high sensitivity RH sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Its sensitivity, linearity, and resolution are 0.5221 dBm/%RH, more than 99% and 0.4094%RH, respectively. In the same year, Irawati et al reported a high sensitivity RH sensor based on the PMMA microfiber doped agarose without any sensitive coating whose sensitivity, linearity and resolution are 0.421 dBm/%RH, more than 98% and 0.431%RH with RH in the range of 50% to 80%RH.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its sensitivity, linearity, and resolution are 0.5221 dBm/%RH, more than 99% and 0.4094%RH, respectively. In the same year, Irawati et al reported a high sensitivity RH sensor based on the PMMA microfiber doped agarose without any sensitive coating whose sensitivity, linearity and resolution are 0.421 dBm/%RH, more than 98% and 0.431%RH with RH in the range of 50% to 80%RH.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Interferometer–based humidity sensors have a high sensitivity and more flexible structure to make it more suitable for practical application. To enhance the sensitivity of humidity sensors, a lot of methods of functionalization have been proposed, such as doped humidity sensitive materials, deposition of functionalized coatings, special structures, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Irawati et al [ 55 ] proposed an optical humidity sensor based on the polymethyl methacrylate (PMMA) microfiber-doped agarose. The doping of agarose gel is enabled by the use of PMMA.…”
Section: Humidity Sensorsmentioning
confidence: 99%
“…To estimate the detection resolution, we use a commonly accepted criterion that shifts of 1/100 of the linewidth can be detected with an adequate signal-to-noise ratio [31,[33][34][35], and obtain the resolution of our sensor to be 0.16% RH, which is better than typical microfiber [9,31,[36][37][38][39] or metallic nanoparticle [40,41] based humidity sensors.…”
Section: Single-cavity-based Optical Rh Sensormentioning
confidence: 99%